Изменение видового состава ихтиофауны Хаджибейского лимана под действием антропогенных факторов и пути её целенаправленного формирования - Шекк, Павел; Shekk, Pavel (Східноєвропейський національний університет імені Лесі Українки, 2015)
Хаджибейский лиман – высокопродуктивный водоём северо-западного Причерноморья. Под влиянием антропогенных факторов водоём последовательно превращался из полигалинного в мезогалинный – олигогалинный – пресноводный и вновь в олигогалинный. Состав ихтиофауны и рыбопродуктивность лимана неоднократно изменялись в зависимости от гидролого-гидрохимического режима водоема, в первую очередь от солености вод. За последние 34 года в лимане встречалось до 21 вида рыб. Многие из них (калкан, угорь, осетр, густера, сом, глосса и др.) попали в лиман случайно либо в результате ограниченной интродукции и встречались редко, иногда единично. В настоящее время лиман представляет собой солоноватоводный водоём-накопитель, что предполагает возможность целенаправленного формирования видового состава ихтиофауны. Hadzibeevsky estuary highly productive reservoir north-west of the Black Sea. Under the influence of anthropogenic factors reservoir experienced a number of periods of consistently turning in poligalinnogo mesohaline – oligogaliny – freshwater and again in oligagalinny. The composition of the fish fauna and fish productivity Hadzibeevsky estuary repeatedly changed depending on the hydrological and hydrochemical regime of the water body and primarily on salinity. Over the last 34 years, in the estuary occurred up to 21 species of fish. Many of them (turbot, eel, sturgeon, bream, catfish, flounder, etc.). Got into the estuary by accident or as a result of the introduction of a limited and rare, sometimes singly and in limited quantities. At present, the estuary is a brackish body of water storage, which implies the possibility of purposeful formation of the species composition of the fish fauna. Promising targets cultivation Khadzhibey estuary include: flounder, sturgeon, salmon, gobies, shrimp. Important area of aquaculture in the estuary - artificial reefs.
Changes in Species Composition of Fish Fauna Hadzibeevsky Estuary Under the Influence of Anthropogenic Factors and Ways of its Purposeful Formation.
Keywords: Хаджибейский лиман; гидролого-гидрохимический режим; состав ихтиофауны; целе-направленное формирование; Khadzhibei estuary; hydrological and hydrochemical conditions; the composition of the fish fauna; purposeful formation